2019
DOI: 10.3389/fpsyg.2019.00081
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Motivational Regulation in Exam Preparation: Results From a Standardized Diary Study

Abstract: Previous studies have shown that the use of motivational regulation strategies has the potential to sustain invested effort and persistence in the learning process. Combining different methods (questionnaires and standardized diaries), the present study aimed to determine the role of motivational regulation in an exam preparation period. Motivational regulation is differentiated in a quantitative (extent of strategy use) and a qualitative (planning, implementing, monitoring, and correcting strategy use) aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
2
26
0
1
Order By: Relevance
“…On the other hand, our results show that the association between intensity and satisfaction with the group learning experience is still present when controlling for immediacy, which suggests that intensity of strategy use does play a role in successful regulation. For motivational regulation problems, this was also demonstrated by Eckerlein et al (2019) who found a direct effect of the frequency of motivational regulation strategies on students' successful regulation of motivational problems in individual selfregulated learning. Further research is still needed to pinpoint the exact conditions under which the frequent use of a broad range of regulation strategies is of particular importance.…”
Section: Problem Perceptionmentioning
confidence: 63%
See 3 more Smart Citations
“…On the other hand, our results show that the association between intensity and satisfaction with the group learning experience is still present when controlling for immediacy, which suggests that intensity of strategy use does play a role in successful regulation. For motivational regulation problems, this was also demonstrated by Eckerlein et al (2019) who found a direct effect of the frequency of motivational regulation strategies on students' successful regulation of motivational problems in individual selfregulated learning. Further research is still needed to pinpoint the exact conditions under which the frequent use of a broad range of regulation strategies is of particular importance.…”
Section: Problem Perceptionmentioning
confidence: 63%
“…Third, it should be noted that some of our operationalizations might be questioned: We based our operationalization of immediacy of strategy use only on theoretical considerations (e.g., based on Eckerlein et al 2019;Hadwin et al 2018). Although future studies might employ a more differentiated coding of the immediacy variable, the fact that satisfaction increased with an increase in all our predictor variables while controlling for problem type actually supports our strategy-problem assignment.…”
Section: Limitations and Conclusionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recent studies have shown that exam results are largely influenced by motivational self-regulation as well as optimal exam preparation strategies (Eckerlein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%